Rapid forming of metallic functional parts - Gong, Thomas Haiqing. (2008)
To develop a high speed machining/prototyping technology (equipment and process) to generate masters from CAD design using soft materials and a 'rapid tooling' technology to convert the soft master pattern to a hard part or tooling made of metal or ceramics.